Analisis Organizational Citizenship Behavior Dalam Upaya Peningkatan Mutu Dosen Perguruan Tinggi Keagamaan Islam Negeri Di Indonesia - Sandra Dewi; Baginda Parsaulian (AKUNTANSI 45, 2022)
The position of work involvement as a mediator influencing the management of personality and grit talents towards OCB is an aspect of theoretical novelty studies. The purpose of this study is the effect of work involvement as a mediating variable between talent management, personality and grit and organizational citizenship behavior. This study uses a quantitative approach with a causal design. The research was conducted through a survey. This research was conducted at 3 PTKIN namely UIN Padang, IAIN Bukittinggi and STAIN Mandailing Natal. The results of this study are First, there is a direct influence between talent, personality and grit management on OCB as shown by the estimated coefficient of each 0.155 (significant at p<0.05 ), 0.310 (significant at p<0.01), 0.268 (significant at p<0.01) and 0.201 (significant at p<0.01). Second, job withdrawal does not mediate the relationship between personality and OCB (VAF=0.190, p<0.01). Third, giving up work did not mediate the relationship between grit and OCB (VAF=0.190, p<0.01). Thus the results of this test reveal that work involvement only mediates the influence of the talent management relationship on OCB, but does not mediate the influence of personality and persistence on OCB.